Global well-posedness of 2D stochastic Burgers equations with multiplicative noise - Jiang-lun Wu (Statistics & Probability Letters, 2022)
In this article, we study 2D stochastic Burgers equations driven by linear multiplicative noise, and with non-periodic boundary conditions. We first apply Galerkin approximation method to show the local existence and uniqueness of strong solutions, we then establish the global well-posedness for strong solutions by utilizing the maximum principle.